An investigation into the first-order factor structure of the personality and preference inventory-normative (PAPI-N) on a relatively large sample of the South African population. - Wilbers, Lizelle (Stellenbosch : Stellenbosch University, 2015)
Thesis (MCom) --Stellenbosch University, 2015.